Controlling Apparent Coordinated Solvent Number in the Perovskite Intermediate Phase Film for Developing Large‐Area Perovskite Solar Modules. Issue 4 (26th September 2019) - Lou, Lingyun; Liu, Tongfa; Xiao, Junyan; Xiao, Shuang; Long, Xia; Zheng, Shizhao; Yang, Shihe
Abstract : Uniform and pinhole‐free organic lead halide perovskite films in a large area are of paramount importance for achieving high power conversion efficiencies (PCEs) of perovskite solar modules (PSMs). To obtain such high‐quality perovskite films in a large area, one commonly needs to prepare a perovskite intermediate phase, in which coordinated solvent number (CSN) seems to be a key parameter. However, the CSN is difficult to measure and control. To understand the relationship between the CSN and perovskite film quality, in situ evolution of the intermediate phase is investigated. The CSN in the intermediate phase film is measured by the high‐accuracy balance. Uniform and pinhole‐free perovskite films are reproducibly formed by tuning the CSN in the intermediate phase film with a mixed antisolvent of ethyl acetate (EA) and toluene (Tol) blended with a 1:1 volume ratio. A hole conductor–free PSM (10 × 10 cm 2 ) thus fabricates and, based on printable carbon electrode, achieves a PCE of 10.2% in 52 cm 2 active area. This effective method provides a promising direction for developing high‐quality and large‐area perovskite films for photovoltaic and other optoelectronic applications. Abstract : A hole conductor–free perovskite solar module with 52 cm 2 active area based on a printable carbon electrode achieves power conversion efficiencies of 10.2%. Coordinated solvent number in the intermediate phase is used to adjust the perovskite nucleation and growth. The uniform and large‐area perovskite film is well controlled by the effective mixed antisolvent method.